Teaching effective pronunciation of plural nouns to English language learners by using a biography driven instruction strategy. - Bajaña Casquete, Erika Liliana (Machala : Universidad Técnica de Machala, 2015)
La sociedad moderna necesita maestros capacitados para ser integrados en el campo de la educación con el fin de responder a los requerimientos y estándares de calidad propuesto en el plan de estudios nacional, los maestros deben tener dominio pedagógico y didáctico para desarrollar las habilidades del estudiante, estas habilidades les ayudarán a hacer frente a nuevos retos en el idioma Inglés lleva en la mayor parte de las actividades del mundo globalizado para hoy.
The modern society needs trained teachers to be integrated to the educational field in order to respond to the requirements and Standards of quality proposed in the National curriculum, teachers must have pedagogical and didactic domain to develop students skills, these skills will help them to face new challenges where the English language leads on the most of the today´s globalized world activities.
Keywords: TEACHING; NOUN; INSTRUCTION; PRONUNCIATION